Estudo metabolômico e anti-inflamatório de Ocotea diospyrifolia (Meisn.) Mez para identificação de suas substâncias ativas e inéditas - Silva, Aline De Fátima (2019)
The Atlantic Forest has a great diversity in its fauna and flora, but has been suffering from deforestation, with the risk of extinction of species that occur exclusively in this region. Since many Atlantic Forest plants have not yet been studied, it is essential to analyze the residual flora of this biome to identify active and unpublished substances. In view of the above, this work aims to study the pharmacological potential of Ocotea diospyrifolia (Meisn.) Mez, native to the Atlantic Forest, in order to identify active and unpublished substances. The plant material was collected in fragments of Atlantic Forest from the city of Alfenas-MG and the extracts were obtained. The evaluation of the anti-inflammatory activity was performed using the ear edema test, besides the quantification of myeloperoxidase. The extracts of the leaves, the acetate fraction from leaves, and essential oils from leaves and bark presented anti-inflammatory activity, while the other types of extract were inactive. From these pharmacological and metabolomic results, the statistical study was carried out and it was possible, through the deregulation, to verify the 39 substances that are significantly correlated with the anti-inflammatory activity investigated, that is, the biomarkers. Ten substances were isolated: mururin A, 5-caffeine ester, neoclorogenic acid methyl ester, quercitrin, salsoline, reticuline, coclaurine, isoboldine, and the compound 9.